Enteroadsorbent Polymethylsiloxane Polyhydrate vs. Probiotic Lactobacillus reuteri DSM 17938 in the Treatment of Rotaviral Gastroenteritis in Infants and Toddlers, a Randomized Controlled Trial - Markovinović, Leo; Knezović, Ivica; Kniewald, Tihana; Stemberger Marić, Lorna; Trkulja, Vladimir; Tešović, Goran (Frontiers in Pediatrics, 2020)
Purpose: The aim of this study was to compare two adjunct therapies in the treatment of childhood rotavirus gastroenteritis (RVGE). We compared the recommended treatment, probiotic Lactobacillus reuteri DSM 17938 (BioGaia®), vs. a novel treatment, enterosorbent polymethylsiloxane polyhydrate (Enterosgel®). Methods: This was an open-label, randomized, clinical controlled trial at the University Hospital for Infectious Diseases (UHID) in Zagreb, Croatia. A total of 149 children aged 6–36 months with acute rotaviral gastroenteritis over a period of <48 h, with no significant chronic comorbidity, were randomized to receive the standard therapy with L. reuteri DSM 17938 (hereafter L. reuteri) or polymethylsiloxane polyhydrate (hereafter PMSPH) therapy, during 5 days. The primary end point was time to recovery in days in both groups. The recovery was defined as absence of fever and vomiting and either the first firm stool, absence of stool for more than 24 h, or return of usual bowel habit. Results: A total of 75 children were randomized into the L. reuteri group and 74 were randomized into the PMSPH group; after excluding missing data, the data from 65 children in each group were analyzed. There was no significant difference in the treatment efficacy between the two regimens with an estimated median time of recovery of 6 days in both groups (p = 0.754). No significant side effects were observed in either group. Conclusion: Novel enterosorbent PMSPH had a similar efficacy to probiotic L. reuteri in the treatment of rotaviral gastroenteritis in preschool children. Clinical Trial Registration:ClinicalTrials.gov Identifier: NCT04116307 [October 3, 2019] (retrospectively registered). https://clinicaltrials.gov/show/NCT04116307.